2011
DOI: 10.1002/hyp.8193
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scale effect on the upper soil effective parameters of a distributed hydrological model

Abstract: Abstract:Nonlinear dynamics and spatial variability in hydrological systems make the formulation of scaling theories difficult. Therefore, the development of knowledge related to scale effects, scaling techniques, parameterization and linkages of parameters across scales is highly relevant. The main purpose of this work is to analyse the spatial effect of the static storage capacity parameter H u and the saturated hydraulic conductivity parameter k s from microscale (sub-grid level) to mesoscale (grid level) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…In other words, the parameter at the fine scale 0 represents the minimum support at which the proposed equations are still valid. Barrios and Francés (2011) indicated that a suitable estimate of 0 for a given parameter could be near its correlation length. The subgrid variability of a parameter β 0 depends, in turn, on the spatial heterogeneity of geophysical and biophysical characteristics (u 0 ), such as terrain elevation, slope and aspect, soil texture, geological formation, and land cover, which are now available at hyper-resolution for the entire globe.…”
Section: The Mpr Approachmentioning
confidence: 99%
“…In other words, the parameter at the fine scale 0 represents the minimum support at which the proposed equations are still valid. Barrios and Francés (2011) indicated that a suitable estimate of 0 for a given parameter could be near its correlation length. The subgrid variability of a parameter β 0 depends, in turn, on the spatial heterogeneity of geophysical and biophysical characteristics (u 0 ), such as terrain elevation, slope and aspect, soil texture, geological formation, and land cover, which are now available at hyper-resolution for the entire globe.…”
Section: The Mpr Approachmentioning
confidence: 99%
“…The variation of rainfall in the basin directly affects the behavior of specific flow discharge. Therefore, the inclusion of rainfall as an explanatory variable of streamflow may be a significant improvement in the regionalization model (DINPASHOH et al, 2004). The climate variable used in regionalization is the average annual rainfall.…”
Section: Streamflow Regionalizationmentioning
confidence: 99%
“…Regression equations are used to estimate streamflows based on the most relevant traits associated with the drainage area (MALEKINEZHAD et al, 2011), but because the gauge stations are located in sections with large drainage areas, the streamflow estimation for small areas is not recommended because of the extrapolation of regression equations. Nonlinear dynamics and spatial variability in hydrological systems make the formulation of scaling theories difficult; therefore, the development of knowledge related to scale effects, scaling techniques, parameterization and linkages of parameters across scales is highly relevant (BARRIOS & FRANCÉS, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear dynamics and spatial variability in hydrological systems make the formulation of scaling theories difficult; therefore, the development of knowledge related to scale effects, scaling techniques, parameterization and linkages of parameters across scales, is highly relevant (BARRIOS & FRANCÉS, 2012). NAGHETTINI & PINTO (2007) note that extrapolating regression equations beyond the limits of sample data used to estimate the parameters of the linear regression model is not usually recommended and has been discouraged for two main reasons.…”
Section: Introductionmentioning
confidence: 99%